On Kant's Idea of Humanity as an End in Itself. (30th August 2013) - Nyholm, Sven
Abstract: Writers like Christine Korsgaard and Allen Wood understand Kant's idea of rational nature as an end in itself as a commitment to a substantive value. This makes it hard for them to explain the supposed equivalence between the universal law and humanity formulations of the categorical imperative, since the former does not appear to assert any substantive value. Nor is it easy for defenders of value‐based readings to explain Kant's claim that the law‐giving nature of practical reason makes all beings with practical reason regard the idea of a rational nature as an end in itself. This article seeks to replace these value‐based readings with a reading of the idea of rational nature as an end that fits better with the overall argument of the Groundwork .